THE ROLE OF MONEY IN THE PURSUIT OF HAPPINESS - Stober, Emmanuel Olusegun (International Journal of Humanity Studies (IJHS), 2023)
Whosoever says money cannot buy you happiness does not know where to shop. Your stand concerning this statement will depend on your level of income and the importance of money for your well-being. Since some might argue that having money is not everything, it then raises the question of what does it take to be happy? What is the government's role in this endeavor? And how can happiness be sustained? This study presents some principles about money and happiness. It suggests that while being rich might not necessarily be the main or only path to happiness, having a higher income will guarantee access to homes in safer neighborhoods, better healthcare, and nutrition, provide access to higher education for your family, give you a sense of fulfillment, work satisfaction, and more leisure time. Note that how you spend, save, and think about money shapes how much joy you get from it. Above all, happiness is a subjective experience. It is about the satisfaction you derive from the way your life is going. Happiness is about personal freedom to make important life choices, such as shaping your life the way you want it.